A comparative study of root cadmium radial transport in seedlings of two wheat (Triticum aestivum L.) genotypes differing in grain cadmium accumulation. (November 2020) - Liu, Yuankun; Lu, Min; Tao, Qi; Luo, Jipeng; Li, Jinxing; Guo, Xinyu; Liang, Yongchao; Yang, Xiaoe; Li, Tingqiang
Abstract: The radial transport of cadmium (Cd) is essential for Cd influx in roots. The role of radial transport pathway on the Cd translocation from root to shoot among wheat genotypes are still poorly understood. This study explored the role of apoplastic and symplastic pathway on root Cd uptake and root-to-shoot translocation in Zhenmai 10 (ZM10, high Cd in grains) and Aikang 58 (AK58, low Cd in grains). Under Cd treatment, the deposition of Casparian strips (CSs) and suberin lamellae (SL) initiated closer to the root apex in ZM10 than that in AK58, which resulted in the lower Cd concentration in apoplastic fluid of ZM10. Simultaneously, Cd-induced expression levels of genes related to Cd uptake in roots were significantly higher in AK58 by contrast with ZM10, contributing to the symplastic Cd accumulation in AK58 root. Moreover, the addition of metabolic inhibitor CCCP noticeably decreased the Cd accumulation in root of both genotypes. Intriguingly, compared to ZM10, greater amounts of Cd were sequestrated in the cell walls and vacuoles in roots of AK58, limiting the translocation of Cd from root to shoot. Furthermore, the elevated TaHMA2 expression in ZM10 indicates that ZM10 had a higher capacity of xylem loading Cd than AK58. All of these results herein suggest that the radial transport is significant for Cd accumulation in roots, but it cannot explain the difference in root-to-shoot translocation of Cd in wheat genotypes with contrast Cd accumulation in grains. Graphical abstract: Image 1 Highlights: CSs formation and suberization is more pronounced in ZM10 than AK58. Long-term Cd exposure mainly affects Cd uptake and transport by symplastic pathway. AK58 limits more Cd in root rather than transfers it into shoot than ZM10. Xylem loading of Cd may be decisive for Cd accumulation in shoots and grains. Abstract : The ability of radial transport, which is of great importance for root Cd accumulation, is not responsible for root-to-shoot translocation of Cd in wheat cultivars. As for high Cd grain accumulation genotype, the content of Cd in ZM10 root was lower, but higher in shoot due to its higher xylem loading ability. In AK58, low Cd grain accumulation genotype, the promoted radial transport led to the higher Cd accumulation in root, which was mainly sequestrated in root vacuolar and cell walls.